2013
DOI: 10.1371/journal.pgen.1003272
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Expansion of Potential Virulence Genes in the Genome of the Oomycete Fish Pathogen Saprolegnia parasitica

Abstract: Oomycetes in the class Saprolegniomycetidae of the Eukaryotic kingdom Stramenopila have evolved as severe pathogens of amphibians, crustaceans, fish and insects, resulting in major losses in aquaculture and damage to aquatic ecosystems. We have sequenced the 63 Mb genome of the fresh water fish pathogen, Saprolegnia parasitica. Approximately 1/3 of the assembled genome exhibits loss of heterozygosity, indicating an efficient mechanism for revealing new variation. Comparison of S. parasitica with plant pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
207
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 170 publications
(222 citation statements)
references
References 78 publications
(134 reference statements)
13
207
1
1
Order By: Relevance
“…The SpCYP51 sequence we identified agreed with that published (SPRG_09493.2) by Jiang et al (51) during the course of our work. TargetP predicted the SpCYP51 N-terminal membrane anchor to consist of the first 36 amino acid residues, while WoLF PSORT predicted that SpCYP51 would be located in the endoplasmic reticulum.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The SpCYP51 sequence we identified agreed with that published (SPRG_09493.2) by Jiang et al (51) during the course of our work. TargetP predicted the SpCYP51 N-terminal membrane anchor to consist of the first 36 amino acid residues, while WoLF PSORT predicted that SpCYP51 would be located in the endoplasmic reticulum.…”
Section: Resultssupporting
confidence: 91%
“…Functional analysis of the lanosterol synthase and ⌬ 5 sterol desaturase candidates (expression, purification, and reconstitution assays) will be required to demonstrate the catalytic function of each protein. The S. parasitica sterol biosynthesis enzymes identified here (Table 4) agree with those identified by Jiang et al (51). However, the sterol pathway proposed by Jiang et al (51) did not relate to the sterols identified in this study.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations